2020
DOI: 10.1111/dth.14498
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive drugs for patients with psoriasis during the COVID ‐19 pandemic era. A review

Abstract: The COVID‐19 has been spreading around the world. Concerns about the safety of administration of immunosuppressive drugs have been raised for treatment of psoriasis (PSO), and there is insufficient evidence for the risk of COVID‐19 infection for psoriatic patients using these drugs, so we did a review, focusing on the risk of overall infection associated with the most commonly used immunosuppressive drugs, such as methotrexate, biologics, cyclosporin, Janus kinase inhibitors for the treatment of PSO. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 50 publications
1
27
0
5
Order By: Relevance
“…Chronic renal failure was also found to be independently associated with poor clinical outcome 38 . Besides, given the long‐standing history of psoriasis in our patient (25 years), we also point out that several studies have found increased risk of serious infection (especially cutaneous and respiratory) in psoriatic patients independently on the therapy and other comorbidities 30,39,40 . The risk of serious infection in psoriatic patients was found to increase further with the severity of the disease 39 and the presence of either diabetes mellitus, obesity, age >60 years, 41,42 or history of smoking 42 .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Chronic renal failure was also found to be independently associated with poor clinical outcome 38 . Besides, given the long‐standing history of psoriasis in our patient (25 years), we also point out that several studies have found increased risk of serious infection (especially cutaneous and respiratory) in psoriatic patients independently on the therapy and other comorbidities 30,39,40 . The risk of serious infection in psoriatic patients was found to increase further with the severity of the disease 39 and the presence of either diabetes mellitus, obesity, age >60 years, 41,42 or history of smoking 42 .…”
Section: Discussionsupporting
confidence: 62%
“…In the other hand, immunosuppression can mitigate excessive inflammation. There are studies showing no increased risk of severe COVID‐19 manifestation in patients on immunosuppressive therapy, including methotrexate, 30,31 as well as reports that emphasize severe COVID‐19 course in such patients 32,33 . Accordingly, available data on the impact of variety of immunosuppressant therapy regarding COVID‐19 clinical course are inconclusive yet 30,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other hand, immunosuppression can mitigate excessive inflammation. There are studies showing no increased risk of severe COVID-19 manifestation in patients on immunosuppressive therapy, including methotrexate 30,31 , as well as reports that emphasize severe COVID-19 course in such patients 32,33 . Accordingly, available data on the impact of variety of immunosuppressant therapy regarding COVID-19 clinical course are inconclusive yet 30,34 .…”
Section: Discussionmentioning
confidence: 99%
“…As officebased phototherapy services may struggle to implement mitigation strategies, home-based phototherapy is an increasingly viable treatment option. 1,4,5 Patient benefits of home therapy include improved treatment compliance; greater patient satisfaction; reduced travel/waiting time; and reduced long-term cost, including co-pays, depending on insurance coverage. 2,4 We aim to provide recommendations on home-based phototherapy during the pandemic.…”
mentioning
confidence: 99%